2010
DOI: 10.1007/s10194-010-0229-9
|View full text |Cite
|
Sign up to set email alerts
|

Headache, epilepsy and photosensitivity: how are they connected?

Abstract: Although headache and epilepsy have often been associated, the precise electroclinical and pathophysiological interaction between these disorders and in particular its relations with photosensitivity is as yet to be fully understood in adults or children. The association between headache and epilepsy commonly occurs in all types of epilepsy and not only in occipital epilepsy. Generally, peri-ictal headache is often neglected, regardless of its severity, because patients are more concerned about their seizures.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 63 publications
(99 reference statements)
2
45
0
Order By: Relevance
“…With regards to the epidemiological literature findings on comorbidity between headache and epilepsy, the major discrepancies and conflicting data are due to: the confusion and mixture of epidemiological data between adults and children across studies, and the significant underestimation of headache when it is comorbid in populations with epilepsy; in addition, it is likely that the comorbidity is higher in children than in adults, as is the case for all other ictal autonomic manifestations [10][11][12]14]. Indeed, the conflicting literature data on this topic can be explained by the co-occurrence (synergistic and/or divergent) of confounding variables according to the different sampling and study design.…”
Section: For Reprint Orders Please Contact Reprints@expert-reviewscommentioning
confidence: 99%
See 3 more Smart Citations
“…With regards to the epidemiological literature findings on comorbidity between headache and epilepsy, the major discrepancies and conflicting data are due to: the confusion and mixture of epidemiological data between adults and children across studies, and the significant underestimation of headache when it is comorbid in populations with epilepsy; in addition, it is likely that the comorbidity is higher in children than in adults, as is the case for all other ictal autonomic manifestations [10][11][12]14]. Indeed, the conflicting literature data on this topic can be explained by the co-occurrence (synergistic and/or divergent) of confounding variables according to the different sampling and study design.…”
Section: For Reprint Orders Please Contact Reprints@expert-reviewscommentioning
confidence: 99%
“…Recently, we have studied this aspect in depth and, due to lack of space, here we refer to the recently published [6][7][8][9][10][11][12]. In this respect, we consider of particular interest the patients reported by Fabricius et al, "…whose seizure activity spread from electrode to electrode at the same slow speed as CSD…" [13].…”
Section: For Reprint Orders Please Contact Reprints@expert-reviewscommentioning
confidence: 99%
See 2 more Smart Citations
“…In addition Clarke et al reported that the increased prevalence of migraine in children with rolandic epilepsy was 15% (20). Several studies have shown that there is an association between occipital lobe epilepsy, especially with photosensitivity, and migraine (21)(22)(23)(24)(25)(26). These findings and close relationship of epilepsy with familial hemiplegic migraine may be explained with possible common genetic mechanisms of the migraine and epilepsy (27).…”
Section: Discussionmentioning
confidence: 99%